2023
DOI: 10.3390/biomedicines11030687
|View full text |Cite
|
Sign up to set email alerts
|

The Third Dose of BNT162b2 COVID-19 Vaccine Does Not “Boost” Disease Flares and Adverse Events in Patients with Rheumatoid Arthritis

Abstract: Data on the risk of adverse events (AEs) and disease flares in autoimmune rheumatic diseases (ARDs) after the third dose of COVID-19 vaccine are scarce. The aim of this multicenter, prospective study is to analyze the clinical and immunological safety of BNT162b2 vaccine in a cohort of rheumatoid arthritis (RA) patients followed-up from the first vaccine cycle to the third dose. The vaccine showed an overall good safety profile with no patient reporting serious AEs, and a low percentage of total AEs at both do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
3
7
1
Order By: Relevance
“…The rate of RA flares in our patients was very low, probably because most were in remission or low activity, in agreement with studies that found an association between flares after vaccination and the disease activity [54,60]. Other authors have also found that COVID-19 vaccines were associated with 4.4%-15.7% of RA flares, and although many of them were mild and self-limiting, in other cases they were moderate-severe and required to make changes to the background treatment in 1.5-30% of cases [51,54,[58][59][60][61][62]. We also found that RA flares were inversely related to age, in line with the study of Ma et al [60].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The rate of RA flares in our patients was very low, probably because most were in remission or low activity, in agreement with studies that found an association between flares after vaccination and the disease activity [54,60]. Other authors have also found that COVID-19 vaccines were associated with 4.4%-15.7% of RA flares, and although many of them were mild and self-limiting, in other cases they were moderate-severe and required to make changes to the background treatment in 1.5-30% of cases [51,54,[58][59][60][61][62]. We also found that RA flares were inversely related to age, in line with the study of Ma et al [60].…”
Section: Discussionsupporting
confidence: 85%
“…The percentage of AEs in our patients was generally lower than that described by other authors, whose values range between 27.7% and 86% [25,51,54,[56][57][58]. Most authors also found that AEs were mostly mild to moderate, although 0.5% to 4.2% serious AEs have been reported [53,58].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Other authors have reported a similar frequency and severity of AEs in patients with autoimmune rheumatic diseases as found in healthy controls and other non-rheumatic autoimmune diseases reinforcing the safety of vaccines in patients with RA [56][57][58]. The percentage of AEs in our patients was generally lower than in literature (27.7-86%) and mostly mild [25,54,[58][59][60][61]. Most authors also found that AEs were mostly mild to moderate, although 0.5%-4.2% serious AEs have been reported [56,61].…”
Section: Safety Of Covid-19 Vaccinessupporting
confidence: 84%
“…He specialized in rheumatology under the guidance of Raffaele D'Amelio, who was then a full Professor of Internal Medicine and is currently retired, and, after the specialization and PhD in Rheumatology, he continued to work at the Sapienza University with Raffaele D'Amelio, who is, after Massimo Fiorilli, the oldest student of Prof. Fernando Aiuti, having started to work in his Laboratory in 1972, one year after his graduation. Andrea Picchianti Diamanti, with a series of co-authors, including Raffaele D'Amelio, Bruno Laganà, Professor of Internal Medicine, who worked with Fernando Aiuti for a short period and with Raffaele D'Amelio for nearly 15 years, Simonetta Salemi, who specialized with Fernando Aiuti and worked with Raffaele D'Amelio for nearly 15 years, and Roberta Di Rosa, who worked with Raffaele D'Amelio for nearly 15 years, provided an interesting paper which demonstrates that a third dose of anti-COVID-19 mRNA vaccine may safely be administered to patients with rheumatoid arthritis, considering that it does not significantly increase disease flares and adverse events [205]. Moreover, it was found that being vaccinated for influenza was inversely associated with the onset of adverse events after the second vaccine dose.…”
mentioning
confidence: 99%